Demyelinating and gliotic cerebellar lesions in Langerhans cell histiocytosis. - Poe, L B; Dubowy, R L; Hochhauser, L; Collins, G H; Crosley, C J; Kanzer, M D; Oliphant, M; Hodge, C J (American Journal of Neuroradiology, 1994)
PURPOSE To describe the involvement of the cerebellum by a gliotic and demyelinating process in Langerhans cell histiocytosis. METHODS A retrospective analysis of all (N = 30) cases of Langerhans cell histiocytosis followed at our institution since 1975 yielded four patients with CT and/or MR evidence of cerebellar abnormalities. RESULTS Four patients manifested strikingly similar findings of symmetric nonenhancing hypodensities in the dentate nuclei region of the cerebellum, which were hypointense on short-repetition-time/short-echo-time MR and hyperintense on long-repetition-time/long-echo-time MR. Biopsy in one patient yielded areas of demyelination, cell loss, and gliosis without histiocytic infiltration. CONCLUSION Langerhans cell histiocytosis involves the cerebellum in a specific and poorly understood manner. Lesions on imaging may precede clinical findings by years. Lesions may occur in patients who have never experienced radiation therapy and may act as a marker for eventual central nervous system deterioration.